DINAMIKA DEMOKRASI LOKAL DI ASIA TENGGARA: DESENTRALISASI, PILKADA, DAN KONFLIK KEKERASAN DI INDONESIA DAN FILIPINA - Rochayati, Nurul (UI Scholars Hub, 2010)
Despite the wave of decentralization that marks strongg democratization and political transition in Indonesia and the Philippines, the violences that occur in the direct elections for local leaders is undoubtly left a big question mark on how democratization could bring peace in the two post-authoritarian cuntries. This article elaborates the phenomenon of political violence in direct elections for local leaders in Indonesia and the Philippines. Bearing in mind that decentralization is the predecessor of the management of direct elections of local leaders, the elections itself aims to elect democratic local government that will be hold accountable in the eye of its constituents in peaceful process. However, the political violence in elections that took form mass demonstrations, burnings, beatings, killings, and other form of violence put questions into the meaning of decentralizing power to local leaders in Indonesia and the Philippines has turnes into the agony of decentralization. It is thus a challenge for both country to prevent the violence to occur in the future to have decentralization work according to its early purpose of promoting good governance at local level.